Optimasi Kesiapan Karier Mahasiswa: Pelatihan Daring Intensif dalam Public Speaking dan Penulisan CV yang Efektif Lingkungan Kerja bagi Mahasiswa - Darmuh, Muthia Mutmainnah; Kadar, Annisa Syauqina (FKIP UKI TORAJA, 2023)
In an increasingly competitive global era, career preparation for senior-level students is a crucial element in achieving success in the dynamic professional world. This research focuses on the implementation of training in four key aspects: public speaking, interview preparation, effective CV writing, and adaptability in the workplace. This study aims to answer two main research questions: How does this training affect the career readiness and competitiveness of senior-level students? The results of the research indicate that this training leads to a significant improvement in public speaking skills, interview preparation, the ability to create standout CVs, and adaptability in the workplace. These findings demonstrate that these trainings successfully equip students with the skills needed to compete in the competitive job market. The discussion delves into the importance of holistic career preparation in facing the increasingly complex job market and fierce competition. The results of this research provide a clear insight into how these trainings can help students achieve early success in their careers